2021
DOI: 10.12688/aasopenres.13247.2
|View full text |Cite
|
Sign up to set email alerts
|

Community-level influences on women’s experience of intimate partner violence and modern contraceptive use in Nigeria: a multilevel analysis of nationally representative survey

Abstract: Background: Modern contraceptives (MC) are important strategies for reducing unwanted pregnancies, unsafe abortion and maternal mortality, but MC remains low at 18% in Nigeria. Similarly, while there is increasing prevalence of intimate partner violence (IPV) in Nigeria, its effects on contraceptive use remain unclear. This study examined the influence of IPV on MC use, while adjusting for individual- and community-level confounders. Methods : The study utilized 2018 Nigeria Demographic and Health Survey data.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…We found the proportions of women who experienced sexual (1.5%), emotional (4.0%) and physical violence (0.08%) in this study. This is contrary to previous studies conducted in Nigeria which reported a larger proportion of women who experienced IPV (7,16). For instance, Solanke (13) reported a higher prevalence of IPV, as well as a study by Adewoyin et al (15) which found 41% physical violence, 38% sexual violence and 29% emotional violence among women in Northern Nigeria.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…We found the proportions of women who experienced sexual (1.5%), emotional (4.0%) and physical violence (0.08%) in this study. This is contrary to previous studies conducted in Nigeria which reported a larger proportion of women who experienced IPV (7,16). For instance, Solanke (13) reported a higher prevalence of IPV, as well as a study by Adewoyin et al (15) which found 41% physical violence, 38% sexual violence and 29% emotional violence among women in Northern Nigeria.…”
Section: Discussionmentioning
confidence: 62%
“…The study further established that women who experienced IPV had lower odds of maternal health care uptake, with non-significant association after controlling for socio-demographic factors. Contrary to expectation, a study in Nigeria (16) found that women who were exposed to intimate partner violence had higher odds of using modern contraceptives. Another study found higher odds of nonuse of modern contraceptives among women not exposed to intimate partner violence (14).…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation